VLC-Based Car-to-Car Communication - Arnez Pramesti Ardi; Ilham Sukma Aulia; Rizky Ardianto Priramadhi; Denny Darlis (Jurnal Elektronika dan Telekomunikasi, 2020)
Based on data from the Indonesian Traffic Corps by September 2019, the number of car accidents was dominated by rear-hit crashes with 6,966 accidents. Most of these accidents occurred during car convoys. It needs a car-to-car communication to increase driver awareness. One of the technologies that can be applied is Visible Light Communication (VLC) and infrared communication. The transmitted data are the vehicle speed data, throttle position, and brake stepping indicator. The data are obtained by reading the Engine Control Unit (ECU) in the car. The data are packaged from the three data and sent to other cars at day and night using VLC and infrared communication. The experimental results show that in a communication system that uses VLC, data can be exchanged between cars during the day up to 2 meters and at night up to 11 meters. Otherwise, in infrared communication, vehicles can communicate during the day up to 2 meters and at night up to 0.7 meter. The test was also carried out with some conditions such as rain, smoke, passers, and other vehicle lights.